Differences among barley row types in β-amylase activity and its dynamics during grain development - CHEN Jin-xin; DAI Fei; WEI Kang; ZHANG Guo-ping (浙江大学学报. 农业与生命科学版, 2005)
Grain β-amylase activity and protein content of 188 barley genotypes with different row type were determined and the dynamics of β-amylase activity during grain development was measured. The results showed that there was a wide variation in grain β-amylase activity among varieties with the same row type, six-rowd type had the highest coefficient of variation among three types of genotypes. β-amylase activity in most barley varieties ranged from 500 U/g to 1500 U/g, and on average of all varieties with the same row type, two-rowed barleys had the highest β-amylase activity. Highly significant positive correlation between β-amylase activity and protein content was found for two-rowed barleys, but not four- and six-rowed barleys. Eight reasonable varieties with β-amylase activity above 1500 U/g and protein content below 11.5% were identified from two-rowed barleys. β-amylase activity showed more rapid increase at early and late grain-filling stage than at medium stage, and the highest activity occurred just at maturity stage. In addition, β-amylase activity was significantly and positively correlated with protein content in the grains during grain development.